A Critical Review on Recent Proposed Automated Programming Assessment Tool - Et.al, Muhammad Huzaifah Ismail (Turkish journal of computer and mathematics education, 2021)
Automated assessment tool for programming assignments has been discussed extensively in education technology ever since of its existence. The tool aims to reduce the work load of instructors as well as providing an instantfeedback to students in pertaining to assessing programming assignments. Myriad versions of the tool accompanied with multiple features has been proposed till this day in order to cater modern trend of education technologies. Many previous studies have analyse on these existing tools but not on recent one. This study have conducted a critical review on the recent proposed tool based on its pedagogical and technical aspect. As a result of this study, more recent proposed tool are identified and its challenging issues are also highlighted.